Improving the Performance of West Java Micro Businesses: The Dual Role of Entrepreneurial Marketing and Digital Marketing - Hidayat, Muhamad; Sondary, Tanty; Ruslan, Syaila Novtasari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines the impact of entrepreneurial marketing on the performance of micro-enterprises in West Java, specifically focusing on the mediating role of digital marketing in this relationship. Using a causal quantitative design, data were collected through a Likert-scale questionnaire distributed to micro-enterprises. The analysis included tests for validity and reliability, difference tests, and mediation tests using sobel and bootstrap procedures. The conceptual framework identifies entrepreneurial marketing which encompasses proactivity, innovation, calculated risk-taking, opportunity orientation, and customer focus as an independent variable that is expected to directly enhance micro enterprise performance and encourage the adoption of digital marketing practices. Digital marketing is defined in terms of the use of social media, marketing content production, digital customer relationship management (CRM), e-commerce platforms, and digital payment systems, all aimed at expanding market reach and improving operational efficiency. The research findings are expected to reveal: (1) a positive influence of entrepreneurial marketing on performance; (2) a positive influence of digital marketing on performance; (3) an impact of entrepreneurial marketing on the adoption of digital marketing; and (4) a mediating role for digital marketing in the relationship between entrepreneurial marketing and micro-enterprise performance.